Green Building as a Strategy for Operational Cost Reduction and Customer Satisfaction - Arsid; Karsam; Atik Budi Paryanti; Ulil Fadilah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Research Objective: To determine the relationship between Green Building and Strategy Operational Cost Reduction and Customer Satisfaction. Research Type: Quantitative research with a descriptive analysis approach. Findings: Green building is an approach that is increasingly being adopted by many organizations as a primary strategy in reducing operational costs while increasing customer satisfaction. This strategy focuses on efficient use of resources, reducing environmental impacts, and creating a better customer experience. Green building integrates energy-efficient and environmentally friendly technologies and designs, Customer satisfaction is one of the important benefits of implementing green buildings. Customers are now increasingly aware of the importance of sustainability and tend to choose companies that care about the environment; a close relationship between reducing operational costs and customer satisfaction through the implementation of green buildings. Theoretical Contribution/Originality: Implementation of green buildings to increase customer satisfaction with cost reduction strategies Practitioner/policy Implications: Green building is an approach that is increasingly being adopted by many organizations as a primary strategy in reducing operational costs while increasing customer satisfaction. Research Limitation/Implications: This article offers a green building concept with a Strategy for Operational Cost Reduction to increase Customer Satisfaction.